Assessment of Social Vulnerability in Malaga Province, Spain: A Comparison of Indicator Standardization Techniques - Gayen, Sumita; Vallejo-Villalta, Luis Ismael; Haque, Sk. Mafizul (Revista de Estudios Andaluces, 2021)
Hazards are any sort of extreme events that occurred by natural causes, human activities or sometimes both reasons are responsible. Social vulnerability exposes people’s condition in hazards. To prevent the loss and damages by hazards, it is necessary to identify vulnerable population of a region by constructing social vulnerability maps of that region. Here in this work, study region is Malaga province, located in southern part of Spain, under the autonomous community of Andalucia. 23 key indicators have been adopted to understand the vulnerability of people in Malaga province at a municipality scale. Three different standardization methodologies (maximum value transformation, z score transformation and min–max rescaling transformation) have been used to build five vulnerable zones. There exists strong to very strong relationship between the results obtained by using three methodologies. The final result shows that most socio-economically vulnerable municipalities are located mainly in western part of the Malaga province.